Grundtvig og den grundlovgivende rigsforsamling - Thaning, Kaj (Grundtvig-Studier, 1949)
Grundtvig and the Constituent Assembly, 1848—49. By Kaj Thaning. Grundtvig developed his political theories in England. In summing up his position with regard to the period from 1815 to 1848 he says: “ Of two evils one must choose the lesser, and freedom without order has always, at any rate since I first saw England, been in my opinion a lesser evil than order without freedom”. His opposition to the movement which was working for a free constitution only meant that he did not believe in “ the artificial, so-called free forms, which if they . . . were to rule unrestricted, would . . . make us all slaves, so that it would only be the freedom of death at the expense of life”. He abhorred and ridiculed the foreign word “ Constitution” and those who shouted loudly for it, but he fought for the freedom of human life, making a sharp distinction between life and forms. The passage which is central for an understanding of his political thought is this: “ Human life demands its rights: its needful sustenance, its beneficial freedom, and its high dignity under all forms of government, and naturally chooses (when it has the choice) the form which at the moment, in accordance with the nature of the people, time and place, seems likely to be most in harmony with the inalienable rights of human life and best to secure the indispensable freedom, necessary balance and ever-advancing enlightenment of that same human life”. The characteristic thing about him is that he will on no account be bound to fixed forms. They must change with the times. People must choose the form which at the moment suits the people, time and place — it is the life of the moment, life in a quite definite situation, that the form must serve. In this sense he is a realist, not an idealist. He is at pains to abjure general political ideas: ideas are always greedy for domination at the expense of life. Holding this view, he stood alone among his political contemporaries. The Conservatives, the men of the absolute monarchy, were overwhelmed by the course of events in 1848 and were obliged unresistingly to watch the old times and the old ideology sink into the grave. Taken by surprise, they submitted to the new state of things. And the Liberals enthusiastically introduced the new ideas after a foreign (mostly Franco-Belgian) pattern, but, when later on they were disappointed because developments did not answer to their bright expectations, they had to cut off a heel here and a toe there to save the system — and their own position — in the country. In reality Grundtvig’s political ideas had greater unity, because he did not idealise forms. Therefore he could, with head up and all the bands playing, go over from his belief in the absolute monarchy as the most popular (“ folkelig” ) form of government to the free Constitution, when it became clear that life could be served by it. In one place he quotes the Englishmen’s only argument for using a particular form: “ it works well”. Grundtvig, also, took the same sober view of the significance of forms, in opposition to the spokesmen of freedom around him, who in his opinion idealised and worshipped forms. Grundtvig has been called an out-and-out Liberal. But the word has many meanings. The National Liberals, his political opponents, were also “ Liberal” . Grundtvig drew a distinction, e.g., between “ the French freedom” which in his opinion was an individualistic conception and had the single individual as its goal, and the English freedom: “he only is free who is willing to let his neighbour be free along with him”. Freedom and inter-connection are here two sides of the same thing. Grundtvig’s “ Liberalism” had an English, not a Continental inspiration. This was of great significance for political development in Denmark. Through Grundtvig’s contribution to politics we get the most living close-up portrait of him which survives. The 4,000 columns of stenographers’ reports in the Parliamentary Gazette (“ Rigsdagstidende” ) for 1848—49 give a vivid impression of the dialogue carried on between Grundtvig and his period. As a writer he occupies an altogether isolated position. In Parliament, too, he stands completely alone, but at the same time in actual converse with his opponents. Sometimes there is a fulmination of retorts, so that the Speaker’s bell has to ring. On the election day itself Grundtvig failed to get elected in the Nyboder division of Copenhagen, where the rival candidate, the head of the Navy, had great influence upon the electors, who chiefly consisted of the men of the fleet. After the election, complaints were made about the indirect pressure which had been exercised upon the electors. (Voting was not by secret ballot at that time.) — But all the same Grundtvig got into the Constituent Assembly — through a bye-election in the Præstø division, his home district. A petition with 2,000 signatures had vainly urged his appointment by the King — a certain number of the members of the Assembly were directly appointed by the King. The new King, Frederik VII — unlike his predecessor — had no special acquaintance with Grundtvig. Grundtvig himself was very pleased at the way in which he got into the Assembly. He was elected with 600 votes against 11, and the election day ended with a festival at which, according to Grundtvig’s description, “ nobleman and clergyman, soldier, citizen and peasant . . . gave each other their hands in the kindly feeling that all Danes are the sons of one mother” . This idyll stood in sharp contrast to the conflict Grundtvig occasioned from the first moment in the Assembly. His first words were a protest — against the truce with the Germans and the general direction of the war —, and his last words were a protest, when in 1866 he, at the age of 83, let himself be elected to the Upper House simply in order to protest against the reactionary revision of the Constitution of 1849. In spite of the fact that he never let himself be captured by any Party, it became increasingly clear that he was the champion of the peasants in weal and woe, so that later on “ the Association of Friends of the Peasants” (“ Bondevennernes Selskab” ) were very glad to see him elected. His chief enemy was, and remained, “the Professors’ Party”, the National Liberals, who in his opinion wanted to misuse the Constitution to consolidate the power of the educated, lacking trust in the people. They put their stamp on the draft Constitution and the electoral law to such an extent that Grundtvig could not vote for either of them. He would not vote for the Constitution because it gave too little freedom. The “monied men” would be able to get power over the Upper House — here Grundtvig foresaw the conflict which eventually came and involved the country in a long, unhappy strife. Even his political opponent, Bishop Monrad, was obliged, many years after Grundtvig’s protest, to acknowledge that he had been right. — But neither would he vote against the Constitution: “ That would have meant siding with those whose views I could least of all share” — i. e., the Conservatives. Grundtvig’s work in the Assembly apparently had no special result. Still, he was one of the few who got something inserted in the draft Constitution. His insertion was: “ Public and oral proceedings shall, as soon and as widely as possible, be put into force in all the administration of justice”. The victory gave him pleasure. But many proposed alterations were rejected, many of them because of his peculiar way of formulating them, which the jurist members disliked. However, many of his ideas have subsequently triumphed. Undoubtedly none of the members of the Constituent Assembly provoked so many different moods in the Assembly as Grundtvig — from the heartiest merriment to fury. His speeches, according to the Parliamentary Gazette, were constantly interrupted by laughter. But sometimes a tumult arose, and once the stenographer had to give in altogether — he simply could not reproduce the commotion aroused by Grundtvig’s speech. The occasion was Grundtvig’s fight against universal military conscription, and it was no doubt the “ Friends of the Peasants” (“ Bondevennerne” ) who made the row. But in return it was also they who interrupted him with shouts of approval when he was attacking the proposal of the Constitution Committee that nothing should be taught “which is in conflict with morality or public order”. Some extracts from this speech give us a glimpse of the extent to which the people responded to Grundtvig’s fight against the State Church with its absolutist stamp, and indeed to his fight for freedom in general. “According to all that I know either of Christianity itself or of its history, it is so far from wishing in any way to limit the freedom of religious belief that it much rather establishes it in the strongest possible way; I am fully convinced that it is never the original, genuine Christianity, but always merely a false and merely a self-made Christianity which tries to obtain a kingdom of this world. (Hear! Hear!) It is always the case that anyone who knows that Christians in all ages have themselves demanded full freedom for their faith and worship of God must also be able to see that if Christianity were to deny the same freedom to others, it would both forfeit its own freedom and at the same time impair the element of freedom in which alone it can breathe and live and thrive. (Spoken like a Christian! Hear! Hear!) . . . the whole of world history teaches us that where this freedom is lacking, no civic freedom can rightly strike root or bear fruit; therefore, if not for its own sake, yet for the sake of all civic and human freedom, one should strive to have it as completely as possible; and if people try to frighten us out of this freedom by enumerating the many dangers which it might bring with it, we should behave as we would if someone tried to frighten the life out of us by enumerating and depicting all the dangers to which human life is undeniably exposed from the cradle to the grave: just as in that case we never ought to give any other answer than: ‘Life is good for everything, and death for nothing; therefore we will keep life and try to avoid and get through its dangers as well as we can’, so we shall also answer here: ‘Freedom is good for all that is good. Slavery is no good for anything that is good in the world of the spirit, therefore we will have freedom with all its dangers’”. Grundtvig left the speaker’s rostrum, greeted with shouts of “ Bravo!” Towards the close of the Constituent Assembly, Grundtvig in a letter to one of his sons surveyed his own part in the proceedings: “ It is a drama which is necessary under the circumstances, and in which I have freely undertaken to play a part on condition of never having to play the part of anybody but myself, and as I have always been doubtful as to how far I should be allowed to enjoy this my inalienable and undefended right, still I observe that on the whole it has been granted to me without grumbling, and, thank God, I believe that even if we seem to be only players, still people do feel it when we are human beings and men who will something good, know what we will, and dare whan we ought . . . So at bottom I have, as always on the whole, good hope and much more boldness to say and do what I consider good and beneficial than ever before ...”